Correlates of cervical cancer screening participation, intention and self-efficacy among Muslim women in southern Ghana - Nancy Innocentia Ebu Enyan; Anita Efua Davies; Rita Opoku-Danso; Francis Annor; Dorcas Obiri-Yeboah (BMC, 2022)
Abstract Background The World Health Organisation's efforts to eliminate cervical cancer by 2030 with a target of 70% screening coverage using a high-performance test demand that women increase participation in screening. Factors that impact uptake of screening must therefore be identified and bottlenecks addressed, especially in lower- and middle-income countries where cervical cancer incidence remains high. This study investigated Muslim women, participation in, intention to engage in and self-efficacy about cervical cancer screening. Methods An analytical cross-sectional study was conducted among Muslim women aged 18 years and above in the Cape Coast Metropolis of Ghana using an interviewer-administered questionnaire. Data were analysed using appropriate descriptive statistics, Chi-square test, point biserial correlation and binary logistic regression analysis. Results The mean age of participants was approximately 31 years (M = 30.9, SD = 10.4). Out of the 431 women, 21 (4.9%) had ever participated in cervical cancer screening. Participants demonstrated very low knowledge about cervical cancer and screening, with a mean knowledge score of 3.68 out of 15. Knowledge about cervical cancer was associated with increased odds of participating in cervical cancer screening (aOR = 1.32, 95%CI 1.11, 1.56). Concerns about similarity with health provider in terms of gender and faith was associated with decreased odds of cervical cancer screening self-efficacy (aOR = 0.81, 95% CI 0.67). Islamic modesty (aOR = 0.88, 95%CI 0.81, 0.96) was associated with decreased self-efficacy about seeking cervical cancer screening, whereas attitude (aOR = 1.32, 95%CI 1.14, 1.53) was significantly associated with increased self-efficacy about seeking cervical cancer screening. Again, Islamic modesty (aOR = 0.88, 95%CI 0.80, 0.97) was associated with decreased intention to participate in screening, whereas attitude (aOR = 1.42, 95%CI 1.20, 1.68) was associated with increased intention to participate in screening. Conclusions There are gaps in knowledge of cervical cancer among Muslim women in this study as less than 5% had participated in screening. A positive attitude was found to influence intention to screen and actual participation in screening programmes. Islamic modesty and commitment to the Islamic faith decreased intention and self-efficacy regarding screening. Therefore, comprehensive and appropriate socio-cultural and religion-specific interventions aimed at addressing the barriers to screening are important in improving uptake among Muslim women.